Penerapan Dutch Angle Dalam Enggambarkan Emosional Pada Film “Tolong Aku” - Nazarruddin Nazarruddin; Dani Manesah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Film, as a genre in the world of cinema, offers a short but captivating audiovisual experience. Films have the potential to create creative, entertaining works and have high artistic value. In the filmmaking process, various techniques and elements are used to improve the quality of the final result. Films are able to convey messages and emotions through various means, including dialogue, visuals, music and special effects. This research focuses on the important role of shooting techniques or cameras in film making. One of the techniques taught is Dutch Angle or Dutch Tilt, which involves tilting the camera angle on a vertical or horizontal axis. This technique is often used in the thriller and horror genres to create a dramatic effect on the audience. The film "Help Me" is an interesting case study, utilizing the Dutch Angle to produce emotions such as sadness, fear, anger, and surprise in the audience. The story of this film tells the story of a student named Dinda who is trapped in an organization that adheres to devil beliefs. Through the use of Dutch Angle, the audience is presented with an unstable atmosphere, creating tension and anxiety that blends with the main character's experiences. The aim of making the film "Help Me" is to apply the Dutch Angle technique to arouse the audience's emotions. In this way, the author hopes to strengthen the message and emotional nuances conveyed through this film. This research also aims to provide an overview of how shooting techniques in films can influence the audience's perception and emotions towards the work.